Wage differentials between native and immigrant women in Spain: Accounting for differences in the supports - Catia Nicodemo; Raul Ramos (Institute for the Study of Labor (IZA), 2011)
The objective of the study is to quantify the wage gap between native and immigrant women in Spain taking into account differences in their characteristics and the need to control for common support. Using the microdata from the Social Security Records (MCVL) and with a matching procedure of \~Nopo (2008) we analysed the decomposition of the wage gap. The advantage of this procedure is that we can simultaneously estimate the common support and the mean counterfactual wage for the women on the common support. In addition, we can describe not only differences at the mean, but along the entire wage distribution. The results obtained indicate that, on average, immigrants women earn less than native in the Spanish labour market. This wage gap is bigger when we analyse the developing countries, but our main finding is that part of this wage gap is related to difference in common supports, i.e. immigrant women have different characteristics than native women that make them less attractive in the labour market. If the need to control for common support is neglected, estimates of the wage gap will be biased.
urn:nbn:de:101:1-201104133933
Keywords: J16; J31; C2; C3; 330; common support; quantile regression; immigration; counterfactual decomposition; Fraueneinkommen; Lohndifferenzierung; Migranten; Bevölkerung; Schätzung; Spanien